Planting Date and Variety Effects on Rice Main and Ratoon Crop Production in South Texas. Issue 21 (29th November 2016) - Dou, Fugen; Tarpley, Lee; Chen, Kun; Wright, Alan L.; Mohammed, Abdul Razack
ABSTRACT: Rice ratooning could be a practical way to increase rice production per unit area and per unit time. The objectives of this study were to evaluate variety [two inbreds (Cocodrie and Presidio) and three hybrids (Clearfield XL729, Clearfield XL745, and XL723)] and planting date (early and normal) effects on rice ratoon production in a sandy loam and clay soil at Eagle Lake and Beaumont, Texas, USA, respectively. A randomized design with four replications was used at both sites in 2008 and 2009 with a total of 160 observations. A PROC MIXED model was used to analyze the data with year and site as random factors and planting date and variety as fixed factors, and main crop (MC) and ratoon crop (RC) were analyzed using Repeated Measures analysis of variance (ANOVA). The grain yield of MC was only affected by the variety with hybrids having greater yields than inbreds (p < 0.01). However, both RC and total (MC plus RC) grain yields were affected by both planting date and variety (p < 0.01). For both RC and TC crops, early planting had greater (10%) grain yields than the normal planting (p < 0.01). Hybrids had 12% greater rain yields than inbreds (p < 0.001), but only for RC. The rice milling quality of MC was also affected by planting date and variety with greater milling yields with inbreds under normal planting. The results from this study indicate that rice ratoon and total crop yields could be improved through a combination of selected management practices including optimal variety selection and an earlier planting date.